If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10x+3/4x=200
We move all terms to the left:
-10x+3/4x-(200)=0
Domain of the equation: 4x!=0We multiply all the terms by the denominator
x!=0/4
x!=0
x∈R
-10x*4x-200*4x+3=0
Wy multiply elements
-40x^2-800x+3=0
a = -40; b = -800; c = +3;
Δ = b2-4ac
Δ = -8002-4·(-40)·3
Δ = 640480
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{640480}=\sqrt{16*40030}=\sqrt{16}*\sqrt{40030}=4\sqrt{40030}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-800)-4\sqrt{40030}}{2*-40}=\frac{800-4\sqrt{40030}}{-80} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-800)+4\sqrt{40030}}{2*-40}=\frac{800+4\sqrt{40030}}{-80} $
| x+81°=4x | | -2/3x=-26 | | 55=25-3p | | 3x+6x(x+3)=3(2x2+7x | | 1/1,000x=2.375 | | -2n-8=2n+4 | | 36p+18+8=35 | | 5(4-5x)=70 | | 3x+6x(x+3)=3(2x^2+7x) | | 1(p-1)=6(p-8)-12 | | -4j=-6-3j | | -4=3f-7 | | -5n+17=4(n+2) | | 32p+18+8=35 | | 4350=448+24x | | -88=2(-5v-4) | | k/k-2=5/7 | | 12y+49=85 | | 12y+49=89 | | 9x-5x-3+10=(9x-5x)+(-3+10)= | | 118=11x-7+5x-3 | | 9x-3+10-5x=9x-5x-3+10= | | 2-b/3=-52 | | 5.50x=58 | | 54=a=22 | | (3*0.7)-1=x | | 3/4x+6=26-(1/2x-10) | | j2− –3=5 | | 4x+3(1-x)=9 | | 61=-4d+9 | | 6+4(x-7)=6x-14 | | 3x+x-3-2=7 |